EU-China engagement in humanitarian aid: Different approaches, shared interests? - Ina Friesen; Leon Janauschek (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
Protracted crises and frequent natural disasters have generated an unprecedented number of people in need of humanitarian assistance. The international community faces a great challenge in supporting these populations, as the gap between needs and available funding is growing. To close this resource gap, the European Union (EU) aims to step up its engagement with emerging donors, particularly China, to increase their level of funding. Although China has previously been reluctant to engage in the international humanitarian system, its response to the COVID-19 pandemic indicates a change in attitude. Over the past year, China has delivered hundreds of tonnes of personal protective equipment (PPE) to over 150 countries and dispatched medical teams abroad. It has also donated 100 million to the World Health Organization (WHO) and the United Nations (UN) and pledged to establish a global humanitarian response depot and hub in China in cooperation with the UN. Amidst increasing geopolitical tensions between China and the EU, China's growing humanitarian engagement opens an opportunity for the EU to engage with China in the humanitarian sector. However, rather than framing China's increased engagement in solely financial terms, the EU should develop a long-term strategy as to how to engage with China on humanitarian matters. A dialogue that takes both parties' different approaches towards humanitarian aid into account and searches for common ground could open the door towards possible cooperation. This would not only help in narrowing the funding gap but carry the potential for greater coordination and consequently more effective assistance provision. China conceptualises humanitarian aid as a subcategory of development aid and provides the majority of its assistance bilaterally. Beijing's state-centric approach to humanitarian assistance means in practice that it engages mostly in the aftermath of natural disasters rather than conflict settings. The EU, on the other hand, has a separate humanitarian aid policy that guides the allocation of funds and provides its humanitarian assistance through non-governmental organisations (NGOs), UN agencies and the International Committee of the Red Cross (ICRC). This Briefing Paper maps out the characteristics of Chinese humanitarian aid and outlines two areas on which the EU's tentative steps towards a dialogue with China could focus. Food security sector: Food insecurity is a key component in existing humanitarian needs, only exacerbated by the COVID-19 pandemic. Food assistance and nutrition are already a key area of engagement for the EU and China. The EU should advocate for China to scale up its contributions to global food security through the World Food Programme (WFP), with whom China has a good working relationship. This could be combined with a political dialogue on how to foster cooperation on food security assistance. Anticipatory humanitarian aid: Disaster risk reduction, preparedness and response play an increasingly important role in global humanitarian aid. China has built up its most significant expertise in response to natural disasters. Enhancement of disaster risk reduction is one of the strategic priorities of the Directorate-General for European Civil Protection and Humanitarian Aid Operations (DG ECHO) for 2020-2024. In light of both parties' interest in anticipatory humanitarian aid, knowledge exchange in this area has the potential to open the door for future cooperation.
Keywords: 330; Humanitäre Hilfe; Internationale Zusammenarbeit; EU-Staaten; China